Applications of Machine Learning Technology in Agricultural Data Mining - Petru Alexandru Vlaicu; Basarab Matei (Applied Sciences)
The global agricultural sector is undergoing a revolutionary transformation with the growing integration of machine learning (ML) technologies into traditional farming and agronomic practices [...]